A promising nucleic acid therapy drug: DNAzymes and its delivery system - Xiao, Lang; Zhao, Yan; Yang, Meng; Luan, Guangxin; Du, Ting; Deng, Shanshan; Jia, Xu (Frontiers in Molecular Biosciences, 2023)
Based on the development of nucleic acid therapeutic drugs, DNAzymes obtained through in vitro selection technology in 1994 are gradually being sought. DNAzymes are single-stranded DNA molecules with catalytic function, which specifically cleave RNA under the action of metal ions. Various in vivo and in vitro models have recently demonstrated that DNAzymes can target related genes in cancer, cardiovascular disease, bacterial and viral infection, and central nervous system disease. Compared with other nucleic acid therapy drugs, DNAzymes have gained more attention due to their excellent cutting efficiency, high stability, and low cost. Here, We first briefly reviewed the development and characteristics of DNAzymes, then discussed disease-targeting inhibition model of DNAzymes, hoping to provide new insights and ways for disease treatment. Finally, DNAzymes were still subject to some restrictions in practical applications, including low cell uptake efficiency, nuclease degradation and interference from other biological matrices. We discussed the latest delivery strategy of DNAzymes, among which lipid nanoparticles have recently received widespread attention due to the successful delivery of the COVID-19 mRNA vaccine, which provides the possibility for the subsequent clinical application of DNAzymes.In addition, the future development of DNAzymes was prospected.